ADOPTION OF DIGITAL TECHNOLOGIES IN THE HIGHER EDUCATION - Abdukadirova Xalida Abduxamedovna; Mukumova Nargis Nuriddinovna (Journal for Technology and Science, 2026)
Objective: This article examines the digital transformation of higher education institutions and their impact on the development of distance education. It analyzes modern approaches to defining the concepts of "university digitalization" and "distance learning technologies," identifying key drivers and barriers to the implementation of digital solutions in the educational process. Method: Based on an analysis of domestic and international experience, the author identifies key areas of digitalization: the implementation of electronic educational platforms, automation of educational process management, and the use of artificial intelligence and big data technologies. Results: Particular attention is paid to the changing roles of teachers and students in the context of the transition to hybrid and fully online learning formats. Novelty: The article identifies key areas of digitalization: the implementation of electronic educational platforms, automation of educational process management, and the use of artificial intelligence and big data technologies.